Marketing of perishable produce Barbados : annotated bibliography - Porsche, Edgar C., comp. (IICA BridgetownBB, 1986)
Consists of entries arranged under the following five headings; crop/project identification; agricultural sector/general; hucksters/public markets; cooperatives and marketing system/supply-demand-prices. Also contains comments on each item.